Features of Social Exclusion and their Relationship with the Trend towards Intellectual Extremism among Young People in Jordanian Society: a Study on a Sample of Mu'tah University Students - Suhemat, Salam; Assasfa, Rami (Dirasat: Human and Social Sciences, 2022)
This study aims at determining the relation of social exclusion (Deprivation of development gains, weak economic participation, weak political participation, unequal distribution of job opportunities) with the trend towards intellectual extremism among youth in Jordanian society. To achieve the goals of the study, the social survey by sample approach was followed using a questionnaire. A random stratified sample by faculty , and a clustered sample at divisions' level were selected and included (549) male and female students (3% of the total society of the study). Results indicated that the role of social exclusion in intellectual extremism among the youth in the Jordanian society from Mu'tah university students' perspective came at high level with a mean of (3.92) with the (weak economic participation) dimension first, followed by the dimension of (Deprivation of development gains,) second , then came the dimension of (unequal distribution of job opportunities) as third, and finally came the dimension of (weak political participation). The study recommended with the necessity of achieving developmental justice among the governorates in the Kingdom, and creating job opportunities for youth, improving opportunities for social integration within society and not to be influenced by disruptive and extremist ideas.